Ecoprint Analysis of Pounding Technique as an Aesthetic Synergy for Art, Culture, and Craft Learning - Sugiastutih, Livia; Restian, Arina; Kuncahyono, Kuncahyono (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2025)
Ecoprint is an art technique that uses natural materials to print patterns or images on media such as fabric or paper, and has recently become increasingly popular in the art world due to its uniqueness and ability to create works connected to nature. This study aims to analyze the application of the ecoprint technique using pounding in visual arts learning for 4th-grade elementary school students. Ecoprint, a technique that utilizes natural materials to imprint patterns on fabric, is gaining popularity in the art world due to its unique and aesthetic results. Visual arts education in 4th-grade elementary school aims to foster creativity in students and introduce art concepts that can be integrated with their surrounding environment. The research used an experimental method with a qualitative approach, where the ecoprint pounding technique is applied to several 4th-grade students. Data was collected through observations and interviews with teachers and students, as well as documentation of the art creation process. The analysis evaluated the effectiveness of this technique in supporting visual arts education while promoting students’ aesthetic development. The results show that the application of the ecoprint pounding technique successfully enhances students’ interest and skills in visual arts. This technique also introduces aesthetic values that connect art with nature, aligning with the goals of visual arts education in elementary schools. In conclusion, ecoprint with the pounding technique can be an effective alternative in visual arts learning in elementary schools, particularly in fostering creativity and students’ aesthetic understanding in 4th-grade classes.